A dominant negative splice variant of the heparan sulfate biosynthesis enzyme NDST1 reduces heparan sulfate sulfation. (7th February 2022) - Missaghian, Parisa; Dierker, Tabea; Khosrowabadi, Elham; Axling, Fredrik; Eriksson, Inger; Ghanem, Abdurrahman; Kusche-Gullberg, Marion; Kellokumpu, Sakari; Kjellén, Lena
Abstract: NDST1 (glucosaminyl N -deacetylase/ N -sulfotransferase) is a key enzyme in heparan sulfate (HS) biosynthesis, where it is responsible for HS N -deacetylation and N -sulfation. In addition to the full length human enzyme of 882 amino acids, here designated NDST1A, a shorter form containing 825 amino acids (NDST1B) is synthesized after alternative splicing of the NDST1 mRNA. NDST1B is mostly expressed at a low level, but increased amounts are seen in several types of cancer where it is associated with shorter survival. In this study, we aimed at characterizing the enzymatic properties of NDST1B and its effect on HS biosynthesis. Purified recombinant NDST1B lacked both N -deacetylase and N -sulfotransferase activities. Interestingly, HEK293 cells overexpressing NDST1B synthesized HS with reduced sulfation and altered domain structure. Fluorescence resonance energy transfer-microscopy demonstrated that both NDST1A and NDST1B had the capacity to interact with the HS copolymerase subunits EXT1 and EXT2 and also to form NDST1A/NDST1B dimers. Since lysates from cells overexpressing NDST1B contained less NDST enzyme activity than control cells, we suggest that NDST1B works in a dominant negative manner, tentatively by replacing the active endogenous NDST1 in the enzyme complexes taking part in biosynthesis.